2004
DOI: 10.1002/pmic.200300773
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics analysis of human endothelial cell line EA.hy926 after exposure to GSM 900 radiation

Abstract: The human endothelial cell line EA.hy926 was exposed to mobile phone radiation and the effect on protein expression was examined using two-dimensional electrophoresis (2-DE). Up to 38 various proteins have statistically significantly altered their expression levels following the irradiation. Four proteins were identified with matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS). Two of the affected proteins were determined to be isoforms of cytoskeletal vimentin. This finding supports our e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 7 publications
7
60
1
1
Order By: Relevance
“…Recent in vitro studies on human sperm and human endothelial cell lines have used 1 hour of in vitro exposure. 53 A decline in ROS levels in semen with time at 37 o C has been demonstrated in a study conducted by Kobayashi et al 54 In a study by Esfandiari et al, ROS levels were significantly higher in semen samples stored at a lower temperature (25 o C vs 37 o C). 55 According to the available guidelines, sensitivity of the experiment should be at the highest level to maximize the possibility of detecting any significant effect(s) of RF-EMW.…”
Section: Dna Integritymentioning
confidence: 97%
“…Recent in vitro studies on human sperm and human endothelial cell lines have used 1 hour of in vitro exposure. 53 A decline in ROS levels in semen with time at 37 o C has been demonstrated in a study conducted by Kobayashi et al 54 In a study by Esfandiari et al, ROS levels were significantly higher in semen samples stored at a lower temperature (25 o C vs 37 o C). 55 According to the available guidelines, sensitivity of the experiment should be at the highest level to maximize the possibility of detecting any significant effect(s) of RF-EMW.…”
Section: Dna Integritymentioning
confidence: 97%
“…Several reports have suggested that some (but not all) vertebrate cell lines may be sensitive to nonthermal effects of RF exposure. These include broad effects on the proteome and specifically on the expression of vimentin isoforms [Nylund & Leszczynski, 2004], as well as on the expression and phosphorylation of small heat-shock proteins (HSP27) in human endothelial cells [Leszczynski et al, 2002]. However, these changes are not seen in several other cell types .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, applications to human exposure assessment do not seem to be common although investigations in vitro with mobile-phone radiation have been reported (30).…”
mentioning
confidence: 99%